3D-Printed On-Fiber Fabry-Pérot Resonator for Refractive Index Measurements - Korec-Kosturek, Joanna; Halendy, Monika; Ertman, Sławomir; Osak, Konrad; Pogorzelec, Konrad; Lesiak, Piotr (Photonics Letters of Poland, 2025)
In this paper, we present the results of measurements performed using a Fabry Pérot resonator printed on a fiber optic tip. Thanks to its design, the resonator allows for simple sputtering of both resonator mirrors with varying degrees of reflection in a single process step. Applying different reflectances to both resonator mirrors significantly increases the refractive index measurement range while maintaining excellent signal modulation (15 dBm for a refractive index of 1.477). Furthermore, our sensor features a wide measurement range (1350-1700 nm).